Introduzione - Marie Fabre; Corinne Manchio; Beatrice Manetti; Francesca Sensini (Laboratoire Italien)
This issue of Laboratoire italien follows a previous one devoted to Voices and Paths of Feminism in Women’s Magazines (1870-1970). It provides an initial appraisal of Italian feminist magazines from the 1970s to the digital turn of the new millennium and the transnational dimension of contemporary feminisms.